On improving the Simplex Coding in the Distributed Raman Fiberwire Sensors - Khokshanov, Naran (2020 International Conference Engineering and Telecommunication (En&T), 2020)
The project is intended to cover main issues pertaining to the area of a signal processing inside the fiberwire Raman sensors. The target of the proposed system is increasing the signal to noise ratio, by means of the simplex coding. The emphasis here is not based on perfecting the Raman sensors scheme, but rather on refining the digital signal processing. The paper will be arranged as follows: analyzing literature, revealed the regularities between the growth of temperature resolution and the simplex coding, computer simulation of the Raman sensors. As a result, the output signal-processing algorithm, which is strengthening the output signal amplitude will be obtained. The question posed will help to understand the simplex coding nature for various scholars.